An Obstetrics Catastrophe Internal Bleeding Following Caesarean Section - Begum, Shahana; Akhtar, Rowshan; Barua, Sharmila; Nath, Bijon Kumar (Journal of Chittagong Medical College Teachers’ Association, 2013)
The objective of this study was to find out the incidence ,indication of primary caesarean section, risk factor, place and expatriation of the primary surgeon and outcome of the cases suffering from internal bleeding following caesarean section in Chittagong Medical College Hospital. This is a prospective observational study carried out in the department of Obstetrics and gynaecology in Chittagong Medical College Hospital from September 2011 to Feb 2012. Over a period of September 2011-Feb 2012 total 11 cases were reported as internal bleeding. Among them 3 patient underwent primary surgery in this institution and 8 patient were referred from outside as internal bleeding following caesarean section. Relaparotomy was done in 10 cases after resuscitation. One patient died before operation. Abdominal cavity was full with huge clotted and non clotted blood in all cases. Bilateral broad ligament hematoma in 45.45% cases. Loosening and disruption of uterine incision in 27.27% cases. Sprouting vessel from mesentery in 9.09% cases. Bleeding from mesenteric vessels in 9.09% cases. Main surgeries performed were subtotal hysterectomy in 36.27% cases. Total abdominal hysterectomy were done in 18.11% cases. Exploration of haematoma and coagulation of sprouting mesenteric vessels with peritoneal toileting in 18.11% cases. Resuturing of uterine incision in 18.11% cases. 63.63% patients were needed ICU support. 45.45% patients died following internal bleeding after caesarean section due to irreversible shock. Though caesarean section is a common obstetrics practice now a days and a life saving procedure for the mother and child but sometimes it complicates as life threatening situation. Repeat laparotomy required in 10 cases within last 6 consecutive month in gynae unit-III in this institution. Case fatality rate was high 45.45%. Near miss mortality was also common. Majority of these were preventable. Identification of risk factor, adequate knowledge about pelvic anatomy, proper attention during primary surgery, expert decision, early diagnosis, prompt intervention and proper case management during laparotomy may improve the outcome. JCMCTA 2013; 24 (1):58-63